ON FUNCTIONAL EQUATION OF ASSOCIATIVITY WITH RIGHT QUASIGROUP OPERATIONS - Shahnazaryan, D.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
We consider equations of associativity and transitivity. We obtain necessary conditions for the solution of these equations for right quasigroup operations, generalizing the classical quasigroup case.